Diagnostic utility of cerebrospinal fluid flow cytometry in patients with and without prior hematologic malignancy. Issue 10 (31st July 2014) - Kovach, Alexandra E.; DeLelys, Michelle E.; Kelliher, Abigail S.; Dillon, Laura J.; Hasserjian, Robert P.; Ferry, Judith A.; Preffer, Frederic I.; Sohani, Aliyah R.
<x xml:space="preserve">Abstract</x> Flow cytometry (FCM) is an adjunct study to routine analysis of cerebrospinal fluid (CSF) to investigate for involvement by a hematologic malignancy. However, in our experience, FCM only infrequently detects abnormalities in CSF. To help optimize resources without forfeiting clinically important data, we sought to determine evidence‐based indications and criteria for performing FCM on CSF. FCM results of 316 consecutive CSF specimens were retrospectively reviewed and correlated with clinical history, total nucleated cell (TNC) counts, and results of concurrent cytologic review. Of 255 samples adequate for analysis, 54% were from patients with a prior history of hematologic malignancy, of which 12% (17 cases) were abnormal by FCM. Corresponding TNC counts among samples with abnormal FCM ranged from 0–1050 cells/µL, and only 44% showed abnormal morphology on concurrent cytology. Of the remaining 46% of samples from patients with no known history of hematologic malignancy who had CSF sampling for neurological indications, only one (1%) was abnormal by FCM. This specimen had an elevated TNC count (39 cells/µL) but lacked clearly abnormal findings on concurrent cytology. These results support the use of CSF FCM only in patients with a history of hematologic malignancy or, in the absence of such a history, in samples showing pleocytosis. If these criteria were applied to the current cohort using a TNC count cut‐off of >5 cells/µL, 23% of samples would have been deferred from testing, resulting in decreased cost, improved efficiency, and reduction in the need for unnecessary testing without a negative impact on clinical care. Am. J. Hematol. 89:978–984, 2014. © 2014 Wiley Periodicals, Inc.